THE ROLE OF NATIONAL VALUES IN THE FORMATION OF MORAL EDUCATION OF THE INDIVIDUAL IN THE FAMILY - Inomjonov Ilkhomjon Shamsiddinovich (Western European Studies, 2024)
This article covers the issues of the role of national values in the formation of moral education of the individual,the work carried out in the education of the younger generation in our country
Keywords: moral education; spiritual heritage; spiritual and moral values